Transformation of Patient Safety Culture through Clinical Communication: A Critical Analysis of Implementing ISBAR3 on Nursing Literature - Husna, Novriani; Said, Faridah Binti Mohd; Nambiar, Nisha (PT. Riset Press International, 2025)
Effective clinical communication is a fundamental element in ensuring patient safety. ISBAR3 (Identification, Situation, Background, Assessment, Recommendation, Read-back, Risk) as a structured communication method has the potential to transform the culture of patient safety in nursing practice. This study critically analyzes the implementation of ISBAR3 in the Indonesian nursing literature for the 2018-2023 period through a qualitative methodology based on a literature study. The results of the analysis revealed the multidimensional impact of ISBAR3 on improving the quality of nursing handover, patient satisfaction, and reducing safety incidents. Factors supporting and inhibiting implementation include teamwork, organizational learning, workload, and management support. Implementation optimization requires a comprehensive approach including contextual adaptation, capacity building, system integration, policy support, and continuous evaluation. The transformation of patient safety culture through ISBAR3 represents a fundamental shift from a reactive to a proactive paradigm in Indonesian healthcare.